CALENDAR AGE OF LISAKOVSKY TIMBERS ATTRIBUTED TO ANDRONOVO COMMUNITY OF BRONZE AGE IN EURASIA - Panyushkina, I.P.; Mills, B.J.; Usmanova, E.R.; Cheng, Li (Published online by Cambridge University Press, 2008)
We measured radiocarbon ages of 22 decadal replications and 1 bulk group from 5 tree-ring specimens using acid-base-acid pretreatment and accelerator mass spectrometry (AMS). The study has the goal of refining the precision and resolution of a segment of the conventional Bronze Age chronology in the Eurasian steppe attributed to the multicultural community known as Andronovo. The archaeological timbers were gathered from 3 cemeteries at the Lisakovsky cluster of sites in Kazakhstan, where there is a prominent Andronovo occurrence that appears to show evidence of overlapping Alakul and Fedorovo cultures in the southern margin of the Eurasian steppe. The new set of Andronovo calendar dates derived from 14C wiggles and a composite floating tree-ring chronology places the cultural overlap from 1780 to 1660 cal BC. Results indicate older ages of artifacts from the Lisakovsky site than were previously determined by the typological chronology, shifting them from the Late Bronze Age to also include the transition between the Middle and Late Bronze Age. The chronological order of the Lisakovsky cemeteries provides strong evidence of contemporaneity of the Alakul and Fedorovo cultures in the Tobol River Valley for a portion of the 120-yr period of occupation. We discuss an application of the dated Alakul-Fedorovo overlap to the relationship and origin of different groups of the Andronovo community in the Ural region. Our results demonstrate the substantial power that tree rings from Bronze Age timbers provide for developing a precise and highly resolved calendar chronology of prehistoric human occupation in the Eurasian steppe during the 2nd millennium BC. © 2008 by the Arizona Board of Regents on behalf of the University of Arizona.
Keywords: CALENDAR AGE; LISAKOVSK TIMBERS; ATTRIBUTED TO ANDRONOVO COMMUNITY; BRONZE AGE; EURASIA